Pembelajaran Tematik Terpadu Tipe Webbed untuk Meningkatkan Keterampilan Berpikir Kritis Sekolah Dasar - Yulia, Rahmi; Fitria, Yanti; Erita, Yeni; Henita, Nofia; Nadia, Deni Okta (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
The purpose of this study was to determine the improvement of critical thinking skills with the application of webbed type integrated thematic learning in elementary schools. The type of research is PTK carried out two cycles referring to the spiral model of C. Kemmis and MC. Taggart. The subject was 28 students of SDN 11 Pudung, Ampek Nagari District, Agam Regency. The instruments used are interviews, observations and tests of learning outcomes in integrated thematic learning. The observation results showed that students in cycle II were more active in group activities than in cycle I. Based on the results of the HOTS test, there was also an increase in student learning outcomes in cycle I with an average of 69,82 and a percentage of KKM 57% which increased in cycle II with an average of 84,82 then the percentage is 82%.